Cultural expressions of the Mama Raywana myth - Falcón Huayta, Victor Eduardo (2022)
The different ways in which an ancient myth of the origin of food has been recorded and survived to these day are exposed. These expressions are concentrated in the central highlands of Peru (Lima, Ancash, Pasco and Huánuco). We find data on the Raywana myth in ethnohistory, ethnography, archeology, and place names. This varied material and immaterial evidence would sustain its conceptual coherence and great influence in the central Andes, assuming a continuity and a prominent place in the Andean religious pantheon up to the present.